Proanthocyanidins, from Ribes nigrum leaves, reduce endothelial adhesion molecules ICAM-1 and VCAM-1 - Desmecht D; Nusgens B; Kinet M; Garbacki N; Damas J (BMC, 2005)
Abstract Background The effects of proanthocyanidins (PACs), isolated from blackcurrant (Ribes nigrum L.) leaves, on neutrophil accumulation during inflammatory processes were investigated in vivo and in vitro. Methods In vivo studies were performed using carrageenin-induced pleurisy in rats pre-treated with PACs. Exudate volume and PMNs accumulation were measured. Leukocyte cell adhesion molecules (LFA-1, Mac-1 and VLA-4) mobilization in circulating granulocytes were analysed by flow cytometry and endothelial cell adhesion molecules (ICAM-1 and VCAM-1) were detected by immunohistochemistry on lung sections. In vitro studies were conducted on endothelial LT2 cells, stimulated with TNF-α, to evaluate ICAM-1, IL-8 and VEGF mRNA expression upon PACs treatment. Data sets were examined by one-way analysis of variance (ANOVA) followed by a Scheffe post-hoc test. Results Pretreatment of the animals with PACs (10, 30 and 60 mg/kg) inhibited dose-dependently carrageenin-induced pleurisy in rats by reducing pleural exudate formation and PMNs infliltration. Leukocyte cell adhesion molecules mobilization was not down-regulated on granulocytes by PACs. Immunohistochemistry on lung sections showed a decreased production of endothelial cell adhesion molecules. In vitro experiments demonstrated that PACs were able to significantly inhibit ICAM-1 but not IL-8 and VEGF165 mRNA expression. Moreover, VEGF121 mRNA expression was dose-dependently enhanced. Conclusion This study provides evidence to support the anti-inflammatory activity of proanthocyanidins is related to an inhibition of leukocyte infiltration which can be explained at least in part by a down-regulation of endothelial adhesion molecules, ICAM-1 and VCAM-1 and that these compounds are capable of modulating TNF-α-induced VEGF transcription.